Дизайн інтер'єру комунікаційних просторів офтальмологічного відділення Лікарні Святого Миколая першого медоб'єднання Львова для дітей, вул. Пилипа Орлика, 4 - Полікровська, Анастасія Русланівна; Polikrovska, Anastasiia Ruslanivna (Національний університет "Львівська політехніка", 2024)
У бакалаврській кваліфікаційній роботі розроблено дизайн інтер’єру комунікаційних просторів дитячого офтальмологічного відділення лікарні Святого Миколая у місті Львів. Проєкт спрямований на створення естетично привабливого, функціонального та безпечного середовища, що враховує психологічні особливості дітей із порушеннями зору та відповідає чинним будівельним нормам і стандартам для медичних закладів. У першому розділі було розглянуто історичні аспекти розвитку архітектури та дизайну медичних закладів, зокрема дитячих лікарень. Проведено аналіз вітчизняних та закордонних аналогів дизайну дитячих лікувальних установ. Другий розділ присвячено вивченню нормативної бази, що регулює проєктування медичних закладів в Україні. Окрему увагу приділено особливостям формування середовища для дітей з офтальмологічними проблемами. Розглянуто принципи формування ергономічного предметно-просторового середовища, з дотриманням усіх вимог та з врахуванням особливостей сприйняття простору дітьми. Третій розділ присвячено опису проєкту дизайну інтер’єру комунікаційних просторів офтальмологічного відділення дитячої лікарні Святого Миколая.

The bachelor's qualification work presents an interior design project for the communication spaces of the children's ophthalmology department at St. Nicholas Hospital in Lviv. The project aims to create an aesthetically appealing, functional, and safe environment that takes into account the psychological needs of children with visual impairments and complies with current building codes and medical facility standards. The first chapter explores the historical development of architecture and design in healthcare facilities, with a particular focus on children's hospitals. It also includes an analysis of both Ukrainian and international design case studies of pediatric medical institutions. The second chapter examines the regulatory framework governing the design of healthcare facilities in Ukraine. Special attention is given to the specific needs of children with ophthalmological conditions, including visual impairments. The chapter outlines the principles for forming an ergonomic and sensory-friendly physical environment, adhering to all applicable standards and considering how children perceive and interact with space. The third chapter describes the proposed interior design project for the communication spaces of the children's ophthalmology department at St. Nicholas Hospital. It highlights the conceptual approach, spatial layout, color schemes, finishing materials, and furniture solutions developed to support the psychological comfort, safety, and navigation for young patients.
Interior design of the communication spaces of the ophthalmology department at St. Nicholas Hospital of the First Medical Association of Lviv for Children, 4 Pylypa Orlyka St.
Keywords: 6.022.03.03; дизайн інтер’єру; дитяча лікарня; медичний простір; офтальмологія; комунікаційні простори; interior design; children's hospital; medical environment; ophthalmology; communication spaces